2009
DOI: 10.1007/s11270-009-0145-2
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Nickel by Means of Micellar-Enhanced Ultrafiltration (MEUF) Using Two Anionic Surfactants

Abstract: Micellar-enhanced ultrafiltration (MEUF) is an effective separation technique for removing metal ions from aqueous environments. The critical micellar concentration (CMC) of two anionic surfactants, sodium dodecyl sulfate (SDS) and linear alkylbenzene sulfonate (LAS), was determined by means of conductometry. The effects of pH, conductivity, and surfactant concentration on the permeate flow, retention of surfactants and nickel by MEUF, was studied. Results showed that for surfactant concentrations beyond the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Some of the physicochemical properties of this anionic surfactant are listed in Table (Samper et al . ; Kowalska ).…”
Section: Methodsmentioning
confidence: 99%
“…Some of the physicochemical properties of this anionic surfactant are listed in Table (Samper et al . ; Kowalska ).…”
Section: Methodsmentioning
confidence: 99%
“…Sodium dodecyl sulfate is found as the effective anionic surfactant for the removal of copper and nickel. Higher removal of copper and (or) nickel were observed in water medium and phosphorous rich synthetic water . Anthati and Marathe demonstrated that copper can be removed effectively by continuous cross‐flow micellar‐enhanced ultrafiltration using iminodiacetic acid (chelating agent) and sodium dodecyl sulfate (anionic surfactant).…”
Section: Removal Of Copper From Water Matricesmentioning
confidence: 99%
“…With increasing pH, the degree of dissociation of RO90 increases (pK A ¼ 4.6) and more carboxy groups become available to bind the Ni 2 þ ions, resulting in a higher metal ion removal efficiency in MEUF. In this contribution we used a pH of 6.5, because this pH was already used in our previous investigation for Cu 2 þ removal [18] and too high pH may lead to precipitation of the metal ions in form of oxides, hydroxides, or oxohydroxides, as mentioned by Samper et al [25]. To estimate how much surfactant is needed to remove the Ni 2 þ ions, we varied the ratio of surfactant to Ni 2 þ (the RO90 concentration was kept constant at 100 cmc).…”
Section: Nickel Removal From Aqueous Streamsmentioning
confidence: 99%